The novel role of the B-cell lymphoma/leukemia 11A (BCL11A) gene in β-thalassaemia treatment - Lai, Mei I; Mahmoud Ahmed, Nahil Hassan (Bentham Science Publishers, 2023)
β-thalassaemia is a genetic disorder resulting in a reduction or absence of β-globin gene expression. Due to the high prevalence of β-thalassaemia and the lack of available treatment other than blood transfusion and haematopoietic stem cell (HSC) transplantation, the disease represents a considerable burden to clinical and economic systems. Foetal haemoglobin has an appreciated ameliorating effect in β-haemoglobinopathy, as the γ-globin chain substitutes the β-globin chain reduction by pairing with the excess α-globin chain in β-thalassaemia and reduces sickling in sickle cell disease (SCD). BCL11A is a critical regulator and repressor of foetal haemoglobin. Down- regulation of BCL11A in adult erythroblasts and cell lines expressing adult haemoglobin led to a significant increase in foetal haemoglobin levels. Disruption of BCL11A erythroid enhancer resulted in disruption of the BCL11A gene solely in the erythroid lineages and increased γ-globin expression in adult erythroid cells. Autologous haematopoietic stem cell gene therapy represents an attractive treatment option to overcome the immune complications and donor availability associated with allogeneic transplantation. Using genome editing technologies, the disruption of BCL11A to induce γ-globin expression in HSCs has emerged as an alternative approach to treat β-thalassaemia. Targeting the +58 BCL11A erythroid enhancer or BCL11A binding motif at the γ -gene promoter with CRISPR-Cas9 or base editors has successfully disrupted the gene and the binding motif with a subsequent increment in HbF levels. This review outlines the critical role of BCL11A in γ-globin gene silencing and discusses the different genome editing approaches to downregulate BCL11A as a means for ameliorating β-thalassaemia.